MODEL PEMBERDAYAAN EKONOMI ALA PESANTREN AL-ITTIFAQ RANCABALI KAB. BANDUNG - R Lukman Fauroni (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2011)
Vocation community based economic is the design to cover centralisticdevelopment program and the boarding school is a social organizationthat exist as creator in developing vocation based economic. Al-Ittifagboarding school has succeed in developing vocation community basedeconomic as part of the program of the boarding school through synergiccooperative vocation in economic and business tutoring so that they buildsuch strong cooperation.